'Creating health': evaluation of three arts for health training events for GP trainees. (September 2021) - Ellis, Vivien; Tully, Katherine; Gill, Nicola; McLewin, Angus; Clift, Stephen
Background: General practitioners (GPs) and other health professionals have a key role in signposting their patients to appropriate opportunities for engaging in arts and creative activities for the health and wellbeing benefits they may bring. Training is needed to ensure that GPs are aware of the evidence supporting the role of the arts, and the local availability of 'creative arts for health' activities for their patients. Aim: This article describes the content and evaluation of three arts and health training events for trainee GPs conducted over the period 2016–2019. They took place in association with Guy's and St Thomas, Hillingdon and York and Scarborough General Practice Vocational Training Schemes (GPVTS). Methods: Evaluation was undertaken for the London events using a specially constructed questionnaire, with rating scales, completed before and after the training events. For the York event, a simple bespoke evaluation questionnaire was employed at the end of the training day. All participants gave consent for photography and filming during the events. Results: Feedback from GPs on the training events revealed increased awareness of the evidence for arts and health interventions, and more positive attitudes towards the role of creative arts in primary care in promoting the health and wellbeing of patients. An additional finding was a recognition by GP trainees that creative activities can enhance a holistic approach to patient care and play a positive part in supporting their own wellbeing. Conclusion: Training events of the kind described, with opportunities for creative participation for GP trainees, can enhance awareness of the benefits of creative activity for patient health and wellbeing, and may motivate future GPs to signpost patients towards opportunities for engaging in creative activities. This training model is applicable for any health worker who can refer patients to arts for health activities and has potential to be scaled up nationally.